The growth effect of democracy: is it heterogenous and how can it be estimated? - Torsten Persson; Guido Tabellini (Center for Economic Studies and ifo Institute (CESifo), 2007)
We estimate the effect of political regime transitions on growth with semi-parametric methods, combining difference in differences with matching, that have not been used in macroeconomic settings. Our semi-parametric estimates suggest that previous parametric estimates may have seriously underestimated the growth effects of democracy. In particular, we find an average negative effect on growth of leaving democracy on the order of ?2 percentage points implying effects on income per capita as large as 45 percent over the 1960- 2000 panel. Heterogenous characteristics of reforming and non-reforming countries appear to play an important role in driving these results.
Keywords: E2; O4; P; 330; Politische Reform; Demokratisierung; Wohlfahrtseffekt; Wirtschaftswachstum; Ökonometrisches Modell; Welt